Repurchase Intentions on Zalora Indonesia: The Role of Trust, E-Commerce and Product Evaluation - Teguh Widodo; Ni Kadek Wahyu Utami (Pusat Penerbitan dan Publikasi Ilmiah, Fakultas Ekonomi dan Bisnis, Universitas Muslim Indonesia, 2021)
The purpose of this study is to explore the impact of trust and e-commerce components, as well as the component of product evaluation, on repurchase intentions at Zalora Indonesia. Adoption of e-commerce is influenced by perceptions of no risk, perceived benefits, and web reputation, while product evaluation is influenced by perceptions of perceived value, product quality, and perceived competitive pricing. For 272 respondents who were distributed via an online questionnaire, convenience sampling with a non-probability sampling technique was used. The test was conducted using the software SmartPLS 3.2.9. The study's findings indicated that the component variables associated with e-commerce adoption were perceived as non-risky and had no effect on repurchase intentions. Perceived benefits and perceived value have the greatest influence on repurchase intention, while perceived trust online has the least. The study's findings have significant implications for understanding how technology adoption and product evaluation can influence repurchase intention.